Antidepressant-like effect of aqueous extract from Rosa damascena in mice - Karim Dolati; Hassan Rakhshandeh; Mohammad Naser Shafei (Mashhad University of Medical Sciences, 2011)
Objective: Rosa damascena mill L (R. damascena) is an ornamental plant that has several therapeutic (such as sedative and hypnotic) effects. It also heals depression, grief, nervous stress and tension. In the present study we evaluated antidepressant-like effect of R. damascena using forced swimming test (FST). Material and Methods: Three doses of aqueous extract (15, 60 and 90 mg/kg) was injected intraperitoneally. After 30 min of injection, immobility and swimming times were measured and compared with control (negative control) and imipramine (positive control). Results: The results showed that low dose (15mg/kg) of extract significantly increased swimming time and decreased immobility time. However, the two high doses of extract (60 and 90mg/kg) had no significant effect on these parameters.  Conclusion: These results proposed antidepressant-like effect of low concentration of aqueous extract of R. damascena.